Pristine Plantain Peels Biochar and Effect of Weathering on Polycyclic Aromatic Hydrocarbon Biodegradation in Crude Oil-Contaminated Soils - Douglas, Reward Kokah; Lawrence, C. A; Ebiundu, K (Transactions on Engineering and Computing Sciences, 2024)
The current research compared the potential of an agricultural waste-plantain peels derived biochar and weathering for the remediation of polycyclic aromatic hydrocarbons (PAHs) contaminated soil at laboratory scale. PAHs concentrations ranged from 0.245 to 348.04 mg/kg for the control sample (concentrations obtained without amendment after 4 day incubation period). Benzo(a)pyrene had the least concentration, while Chrysene has the highest concentration. Under weathering conditions, the sum concentration of PAHs were observed to be 694.213, 687.892, and 670.866 mg/kg after 30, 60, and 90 days experiment, respectively. More PAHs concentration degradation was observed PPB amendment option. That is, with PPB amendment option, the sum concentration of PAHs obtained were 649.743, 634.532, and 550.369 mg/kg after 30, 60, and 90 day experiment, respectively. Furthermore, first-order kinetics was used to determine the kinetics of PAHs degradation, which was applied on both the weathering and the PPB amendment options. With weathering, PAHs degradation rate constant (K) increased with decreasing PAHs concentrations; which shows that PAHs degradation in contaminated soil is slow under the influence of weathering. With PPB amendment option, the K value decreased between K30 and K60 with decreasing PAHs concentrations, which implies faster degradation of PAHs. However, reverse was the case between K60 and K90. This shows slow degradation of PAHs. Results suggest that the PPB option is best for the restoration and/or reclamation of soil polluted with PAHs.